Optimasi Pengelolaan Data Pencarian Fasilitas Ekspedisi Berbasis Otomasi dengan Pendekatan Framework Waterfall - Yulyanti, Eva; Shindy Yuliyatini; Imelda, Imelda (Jurnal Informatika & Teknologi Cerdas, 2025)
Information technology (IT) has become an integral part of everyday life and plays an important role in various aspects of modern society. With the rapid development of technology, IT has changed the way individuals and organizations communicate, work, and interact. PT XYZ, as a company engaged in logistics, faces a challenge in managing expedition facility search data. This study aims to automate the management of expedition facility search data using the Waterfall framework. The stages in Waterfall include stages such as needs analysis, design, implementation, testing and maintenance. The waterfall method is helpful because it provides a structured, clear, and organized process for project completion.